AN EXPERIMENTAL STUDY ON FIBER REINFORCED SELF COMPACTING CONCRETE INCORPORATED WITH SINTERED FLY ASH AGGREGATE (International Journal of Food and Nutritional Sciences, 2022)
The development of new type of high performance concrete, such as self- compacting concrete (SCC) or lightweight concrete (LWC) responds to some requirements of the construction industry. Due to the reduced weight LWCs have other advantages compared to normal-weight concrete, such as good fire resistance and improved heat insulation. Sintered fly ash aggregate is the best for the use in structural applications. In addition to the light weight aggregate fibres which are best known for resisting cracks, fatigue , bending , durability etc are also included to get more effective outputs from the members. Fibre reinforced concrete were developed to overcome the cracks and to provide additional strength. SCC is cast so that there is no additional vibration, necessary for the compaction. It has a high flowing property and has a very smooth surface level after placing. SCC has several advantages over normal conventional concrete and so thus SCC reinforced with steel fibre. It can flow easily in congested reinforced areas such as in beam column points. Hence the combination of SCC with steel fiber is a concrete mixture with dual advantage. In this project the hooked end steel fibers of 0.75mm Dia and 50mm length are added in reinforced concrete beam with concrete compressive strength of 30MPa (M30). The optimum percentage of 1% steel fibers added to concrete mix and sintered fly ash aggregates are replacing to the coarse aggregate with different percentages (i.e 0%, 10%, 20%, 30%) have been tested. Specimen were casted with fibres and sintered fly ash aggregate , allowed to cure for a period of 28 days and tested.